ANALISIS FAKTOR PERNIKAHAN ANAK USIA DINI MENURUT PERSEPSI MASYARAKAT - Hasan Slamet (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2022)
Child marriage is still often referred to as early childhood marriage which is a problem at this time, until now there are still many marriages carried out by minors for various reasons and purposes. Marriage is sunnatullah but in practice, marriages carried out in early childhood have various problems that accompany them, both in health, psychological and others. Therefore this study wants to examine and analyze the occurrence of early marriage based on public perception, using quantitative analysis, which is analyzed by correlation and regression analysis. The researcher succeeded in collecting 102 research samples. From the results of the study it was found that economic factors, parents, accidents (married by accident), education, mass media, local customs have a relationship to early child marriage, mass media factors are factors that provide the biggest role in the occurrence of early child marriage in the community and followed by parental factors, economic factors, accident factors (married by accident), cultural factors and finally educational factors, this study shows an increase in the percentage to 59.6% of early child marriage influenced by mass media factors, economic factors, and parental factors from this study proves that mass media factors, economic factors and parental factors have a big role in early child marriage. Thus, according to the community, the causes or factors that have a major impact on the occurrence of early childhood marriage are caused by mass media factors, economic factors and parental factors.